2015
DOI: 10.1590/1516-635x1701109-116
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between linear and nonlinear systems of feed formulation for broilers

Abstract: Two experiments were simultaneously carried out to compare feed formulation models: a linear model for minimum cost with a nonlinear model for maximum profitability for one-to 42-d-old broilers. One-dold male or female Cobb 500 broilers (n=2368) were allocated to one of the two trials according to sex. The experiments were performed simultaneously in an experimental poultry farm. Two housing densities were used: high density (HDH), with 14 birds/m 2 , and low density (LDH), with 10 birds/m 2 . The following tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The lower feed intake and higher egg mass observed in the Models treatment resulted in improved feed conversion ratio. However, optimal feed conversion ratio does not necessarily mean lower production costs (Dadalt et al, 2015). The Favorable treatment resulted in worse feed conversion compared with the Models treatment, but generated higher profit.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The lower feed intake and higher egg mass observed in the Models treatment resulted in improved feed conversion ratio. However, optimal feed conversion ratio does not necessarily mean lower production costs (Dadalt et al, 2015). The Favorable treatment resulted in worse feed conversion compared with the Models treatment, but generated higher profit.…”
Section: Discussionmentioning
confidence: 96%
“…The results of the present study are consistent with those of Afrouziyeh et al (2010) and Afrouziyeh et al (2011), who obtained higher profitability with using non-linear programming to formulate diets for laying hens of 24 to 32 weeks of age and 32 to 44 weeks of age, respectively. In broilers, other authors (Heydari, 2014;Dadalt et al, 2015;Gonçalves et al, 2015), evaluating feed formulation for maximum profit, also observed that the better live performance provided by minimum cost feeds does not generate maximum profitability of the production system. This is due to the greater nutritional level flexibility provided by non-linear programming, which establishes the required nutritional levels to obtain the highest profit according to the economic scenario (Guevara, 2004;Eits et al, 2005).Therefore, feed formulation using non-linear programming may be an alternative method to minimum cost feed formulation due to the program's ability to combine principles of precision nutrition (Cerrate & Waldroup, 2009;Gonçalves et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation